Poisson point process-based network modelling and performance analysis of multi-hop D2D chain relay formation in heterogeneous wireless network. (2019) - Chakrabarti, Subhankar; Das, Susmita
This article presents stochastic geometry-based unified analytical framework to analyse the functionality of device-to-device (D2D) assisted cellular network in inband overlay mode. Independent marked Poisson point process (imPPP) is incorporated to probabilistically model the aggregate interference and SINR distribution of the randomly distributed nodes in the spatial domain. The proposed framework is applied to evaluate the overall network coverage probability improvement due to minimisation of congestion in the base station oriented core network by involving more devices in direct communication (through traffic offloading). Statistical analysis of slotted-synchronous and slotted-asynchronous traffic patterns in terms of throughput for varying transmission probability is also presented. From the application point of view, in the case of base station service interruption due to any natural calamity or power failure, the proposed multi-hop D2D chain relay formation helps to extend the cellular coverage in cell edges as well as in adjacent affected cell areas.